2014
DOI: 10.1186/1472-6882-14-160
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for managing knee osteoarthritis in older women: a pilot randomized controlled trial

Abstract: BackgroundOsteoarthritis (OA) is a common problem in older women that is associated with pain and disabilities. Although yoga is recommended as an exercise intervention to manage arthritis, there is limited evidence documenting its effectiveness, with little known about its long term benefits. This study’s aims were to assess the feasibility and potential efficacy of a Hatha yoga exercise program in managing OA-related symptoms in older women with knee OA.MethodsEligible participants (N = 36; mean age 72 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
185
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(192 citation statements)
references
References 23 publications
4
185
0
3
Order By: Relevance
“…Data from a recent pilot study [36] indicated an overall SD of 16.5 for the total WOMAC and a correlation between time points of 0.6. The sample size of 30 per group was calculated to have 80% power to detect a difference in the change (slope) of 35% over time (change of 11.3 on the WOMAC total score) with Type I error set to 0.05 and using a repeated measures analysis of covariance (ANCOVA) controlling for baseline values.…”
Section: Methodsmentioning
confidence: 99%
“…Data from a recent pilot study [36] indicated an overall SD of 16.5 for the total WOMAC and a correlation between time points of 0.6. The sample size of 30 per group was calculated to have 80% power to detect a difference in the change (slope) of 35% over time (change of 11.3 on the WOMAC total score) with Type I error set to 0.05 and using a repeated measures analysis of covariance (ANCOVA) controlling for baseline values.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that Hatha yoga practice is better than therapeutic exercise on all of these variables for patients with knee osteoarthritis. In another randomized controlled study on knee osteoarthritis in older women, the participants were randomly assigned to an eight week yoga program involving group and home sessions or to a waitlist control group [84]. The yoga group outperformed the waitlist control group on reduction in pain, stiffness, and sleep disturbances by the end of 20 weeks of treatment.…”
Section: Knee Osteoarthritismentioning
confidence: 99%
“…Yapılan çalışmalarda, diz OA'da konvansiyonel tedavi ile birlikte uygulanan yoganın ağrıyı azalttığı, sürekli kaygı durumu üzerinde etkili olduğu, fonksiyonel düzeyi arttırdığı, günlük aktiviteler, spor, boş zaman faaliyetleri ve yaşam kalitesini yükselttiği belirtilmiştir [33][34][35][36]. Yapılan bir meta-analizde yoganın ağrı ve sakatlık için yararlı bir yaklaşım olduğu gösterilmiştir [37].…”
Section: Yogaunclassified
“…Yapılan bir meta-analizde yoganın ağrı ve sakatlık için yararlı bir yaklaşım olduğu gösterilmiştir [37]. Yoga diz OA'lı bireylerin durumunu iyileştirmek için medikal tedaviye ek olarak uygulanabilecek güvenilir yöntemlerden biridir [34,36].…”
Section: Yogaunclassified